C'EST GOUVERNANCE PARLEMENTAIRE, RADIOSCOPIE DE LA FONCTION CONTRÔLE DE L'ASSEMBLÉE PROVINCIALE DU MANIEMA PENDANT LA PREMIERE LEGISLATURE - CT. Victor NONGA WALEMBA,; Ass. Emmanuel SALEH KANDAKE -KANSAL, (IJRDO - Journal of Social Science and Humanities Research, 2019)
Parliamentary governance, let us remember, is the central theme of our reflection. It is in fact a review of the parliamentary oversight function during the first legislature, which focused on three main points:In the first, the study shows that the legal basis of the parliamentary control function remains in conformity with the constitution of the DR Congo. Indeed, his articles197 and 198 confirm this state of affairs.            In the second, the study sets out the means or control mechanisms legally recognized by the Assemblies, in this case the Maniema (oral questions, arrests, commissions, ...) and the related sanctions.             In the third, the study makes an inventory of the actions carried out in the field of parliamentary control. Indeed, it is clear that the Provincial Assembly of Maniema in the first legislature reached a score of 67 oral questions with debate, 17 commissions of inquiry, 5 arrests and 4 motions including 03 of distrust and 01 of censorship. Given all the reasons given and in view of the actions carried out, it is necessary to note a "relative efficiency" of the control function of the Provincial Assembly of Maniema with regard to the time allotted to it (12 years of exercise) and the gravities in face (amateurism of deputies, deficit of the culture of the good governance, bad interpretation or application of the internal rules, precarious financial and material, political pressures, political patronage ...).Thus, for a more effective parliamentary oversight function during the second legislature, the study suggests some possible solutions, namely: the awareness of the provincial deputies on the usefulness of the parliamentary oversight function, the capacity building of the provincial deputies and the de-politicization of the parliamentary control function.